2016
DOI: 10.3748/wjg.v22.i43.9631
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of colorectal cancer screening: Participantsvsindividuals not invited

Abstract: AIMTo investigate the possible long-term psychological harm of participating in colorectal cancer (CRC) screening in Norway.METHODSIn a prospective, randomized trial, 14294 participants (aged 50-74 years) were invited to either flexible sigmoidoscopy (FS) screening, or a faecal immunochemical test (FIT) (1:1). In total, 4422 screening participants (32%) completed the questionnaire, which consisted of the Hospital Anxiety and Depression Scale and the SF-12, a generic health-related quality of life (HRQOL) measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…In contrast, in the BCSN pilot study, Kirkoen et al 2016 [35] reported a statistically significant decrease in symptoms of anxiety following receipt of negative flexible sigmoidoscopy or FIT results in participants. In addition, Korfage et al 2012 [17] [46], while there was a statistically significant increase in symptoms of anxiety in individuals with normal results, there were fewer individuals with a clinically significant increase in symptoms of anxiety (i.e., MCID = 1 standard error of measurement) after receiving normal results compared to the number of individuals with an increase in symptoms of anxiety prior to receipt of results.…”
Section: Impact Of Normal Screening Results On Symptoms Of Anxietymentioning
confidence: 90%
“…In contrast, in the BCSN pilot study, Kirkoen et al 2016 [35] reported a statistically significant decrease in symptoms of anxiety following receipt of negative flexible sigmoidoscopy or FIT results in participants. In addition, Korfage et al 2012 [17] [46], while there was a statistically significant increase in symptoms of anxiety in individuals with normal results, there were fewer individuals with a clinically significant increase in symptoms of anxiety (i.e., MCID = 1 standard error of measurement) after receiving normal results compared to the number of individuals with an increase in symptoms of anxiety prior to receipt of results.…”
Section: Impact Of Normal Screening Results On Symptoms Of Anxietymentioning
confidence: 90%
“…As CRC screening program is still in its early stages in Malaysia, there has been no previous local survey on the QOL of the population undergoing a CRC screening. Whereas previous studies at the international level regarding the CRC screening were more focused on QOL studies after the screening results were obtained and revealed (Kapidzic et al 2012;Kirkoen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, there seems to be a gap in the scientific literature especially on the psychosocial factors that might influence patient’s decision to undergo or refuse CRC screening. In particular, knowledge of the psychological effects on participating in CRC screening is limited and there are few studies, with mixed and contradictory results, that have tried to aassess which psychological aspects such as fear can affect the probability that patients undergo specific screening and how much participants may experience psychological stress from participation even after a long time [ 30 ].…”
Section: Reasons For Non-adherence To Colorectal Cancer Screeningmentioning
confidence: 99%